Modeling of Moth Eye Structures for Silicon Solar Cells Efficiency Enhancement - Jasim , Ethar; Khaleel, Imad hadi; Al-Shawabkeh, Ali F. Al-Shawabkeh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Moth-eye nano-structure is essentially used as a light-trapping technique for more efficient and cost-effective solar cells. This computational study investigated two dimensions of rectangular silicon base anti-reflected nanostructure for ultra-thin film solar silicon cell efficiency enhancement. The introduced simulation procedure depends on numerical methods and Lumerical software. Impacts of the structure geometry, which was the width and height, on optical and electrical properties were investigated. It found that the geometry of the structure has a significant effect on the absorption and reflection spectrum, due to structure light-trapping effects, and the maximum absorption increases in visible regain reported at a width of 300 nm and height of 100 nm. We also determined the fill factor, short circuit current, and open circuit voltage. It is found that the short circuit current density is significantly influenced by the structure geometry due to a change in absorption, which influences electron-hole generation. It’s also found that the performance can be enhanced by choosing a suitable dimension for the suggested structure. The optimum efficiency enhancement achieved was from 8.71% to 11.89%, and the obtained results are encouraging for using the presented procedure to design more complex structures.